2018
DOI: 10.4102/td.v14i1.356
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of municipal e-government readiness using structural equation modelling technique

Abstract: The evaluation of municipal e-government readiness can provide a useful barometer to understand the critical needs of citizens. In addition, it can help to improve effectiveness of government services and provide a technology industry access to relevant information to create efficient e-services. This study develops and tests a framework to evaluate municipal e-government readiness based on building blocks of supporting e-services readiness, individual citizen readiness, municipal government readiness, technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Consequently, the continues advancing in technologies needs assessing the impact of any rising technology on eGovernment adoption. [11] said that the high impact of the technology infrastructure eReadiness emphasizes that technology is that the main supply of modification and provides power for enabling the method of implementing eGovernment initiatives. [12] The result showed that there's a positive important relationship between technological readiness and also the IT competencies of Iraqi accountants.…”
Section: Proposed Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the continues advancing in technologies needs assessing the impact of any rising technology on eGovernment adoption. [11] said that the high impact of the technology infrastructure eReadiness emphasizes that technology is that the main supply of modification and provides power for enabling the method of implementing eGovernment initiatives. [12] The result showed that there's a positive important relationship between technological readiness and also the IT competencies of Iraqi accountants.…”
Section: Proposed Frameworkmentioning
confidence: 99%
“…[16] see that Culture issue had considerably influenced the intention of SMEs to use eGovernment services. [11] said that eGovernment should be nationally orientated. In general, lack of competency of government staff in using ICT, low level of eGovernment awareness among the voters and lack of motivation are the most important obstacles for the roaring implementation of eGovernment at the municipal level.…”
Section: Proposed Frameworkmentioning
confidence: 99%